Ecology, Culture, and Behavior: Role in Societal Development. (February 2023) - Berry, John W.
The field of cross-cultural psychology studies the development and display of human behavior as it emerges in various ecological and cultural contexts worldwide. I adopt two perspectives on this field: functionalism and universalism. The first perspective considers that individual behaviors are adaptive to these contexts in variable ways that permit success in life; that is, adaptation involves changing societal institutions and behaviors over time to meet the needs and goals of local cultural populations. The second perspective views these behaviors as being rooted in species-wide shared processes and capacities; that is, all human beings possess a set of common underlying potentials for development. From these two perspectives, I see no contradiction between evidence that behaviors are differentially shaped, developed, and expressed in different cultures, and the evidence that there are shared underlying processes on which these developments take place. Culturally sensitive development, when viewed within this conceptual nexus, is not a "one size fits all" approach, but one that is rooted in, and meets, both local and global needs and concerns.